First record of Choragus sheppardi Kirby, 1818 (Coleoptera, Anthribidae) in Volyn Region - Nazarenko, Vitaly; Sukhomlin, Kateryna B.; Zinchenko, Oleksandr P.; Trush, Tatiana (Волинський національний університет імені Лесі Українки, 2024)
Choragus cheppardi inhabits western Palearctic. In Ukraine, this species was found only in the southern and eastern parts (Crimea in 1980 and 2003, Kharkiv region in 1998, Donetsk, Lugansk regions in 2000). Lives in nemoral and mixed forests on deciduous trees (Fagus sylvatica, Hedera helix, Malus domestica, Crataegus monogyna, Ulmus glabra, Sorbus aucuparia, Quercus spp., Alnus glutinosa, Salix spp.). Larvae start their development in summer in the pycnidia of the Diatrype stigma (crust fungi, Diatrypaceae). Adults occur in IV–VIII (IX by our original data). Emerged adults overwintering and start new generation in spring, mostly in April. The collection of material was carried out by counting animals on six test plots from 05.07.2022 to 09.25.2022. Three Barber traps were placed in each trial area. The traps were located at a distance of 50 m from each other. New find of Ch. cheppardi was registered in the Kivertsi National Park "Tsumanska Pushcha". 1 male was collected in a birch forest mixed with alder. Current find of this species confirm previously published data on its occurrence in the in nemoral and mixed forests. It can be expected that Ch. cheppardi can be found in other places of Ukraine.
Keywords: Choragus cheppardi; birch and alder forests; Kivertsi National Park «Tsumanska Pushcha»; 595.768.23